Impact of contraceptive counselling training among counsellors participating in the FIGO postpartum intrauterine device initiative in Bangladesh. (18th September 2018) - Fatima, Parveen; Antora, Arefa Hossain; Dewan, Farhana; Nash, Stephen; Sethi, Maya
Abstract: Objective: To evaluate the impact of structured training given to dedicated family planning counsellors on postpartum intrauterine device (PPIUD) services across six tertiary hospitals in Bangladesh. Methods: Family planning counsellors underwent structured training on postpartum family planning, PPIUD in particular, over a four‐day period. Impact of training was evaluated by comparing PPIUD counselling rates, consent rates, insertion rates, and removal rates five months before and five months after the training, using data from women delivering in the participating facilities. Results: A total of 27 622 women were included in this analysis: 11 263 (40.8%) before the training intervention and 16 359 (59.2%) after it. There was an increase in the proportion of women who were counselled (from 75.3% to 83.8%, P <0.001), and a small decrease in the proportion of women agreeing to have a PPIUD inserted following counselling (13.7% vs 12.9%, P =0.03). Overall insertion rate was similar before and after training (9.5% vs 9.8%, P =0.42), while removal rate reduced from 2.8% to 1.8% ( P =0.41). Conclusion: Structured training had no impact on overall PPIUD insertion rate. However, it did impact numbers of women receiving counselling, perceived quality of the counselling received, and overall removal rates. Abstract : Although structured training had no impact on overall insertion rate, it did impact numbers of women receiving counselling, perceived quality of counselling, and overall removal rates.